(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
While optimising the waste management, the Region waste management system – the system of regional waste management centres was created in Lithuania. Utena regional landfill is one of its elements. Since 2010 the waste flows were started to calculate by different fractions. Visually observing the waste disposal, it was noticed that the proportions of unsorted waste quantities flows were different in the districts, so it was decided that the custom random works of the mixed municipal waste content determination will be carried out in 2012 and 2013 four times a year, in different seasons. There is a possibility to dispose the sorted waste in Lithuania. Also, in all the municipalities there are Bulky and hazardous waste receiving and temporary storage sites, where the hazardous waste can be delivered. However, it was noticed that the sorting is insufficient – among the mixed municipal waste there are improper waste to be deposited, including the hazardous waste. The aim of the work is to analyze the change of the waste quantities at Utena regional landfill, distinguishing the quantities of the hazardous waste.